If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 1) + -1 = 0 Reorder the terms: -1(1 + x) + -1 = 0 (1 * -1 + x * -1) + -1 = 0 (-1 + -1x) + -1 = 0 Reorder the terms: -1 + -1 + -1x = 0 Combine like terms: -1 + -1 = -2 -2 + -1x = 0 Solving -2 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| -(-y-4w+3)= | | (3y)=x-2x | | -5(-1)(-3)(-3)= | | 6(11-2)=54 | | P+9=56 | | 7+3*x=31 | | P+a=56 | | (3y)=x-2xsquared | | P+a=55 | | 5n-10=37 | | X=63-x/0.4 | | -3+(N+1)=12 | | wn2/3w=5/8 | | Log(9x+7)=1 | | (h+9)=2x-6 | | N+[4-2(3-5)]=6 | | bj=104 | | -17+a=-(-10) | | 1=3.5t | | 0.75(12x+8)=2x-15 | | .19*.23=x | | .19*.23= | | 2x-5=27-6x | | 3(u+3)-7u=37 | | (4s)^5/(4s)^12 | | 2xn=8xn+30 | | 164=121-y | | 50*25h=125 | | -0.3333333333=75-15 | | a/5-5/6=-1/2 | | 4x^3-4x^2-9x+12=0 | | -20c=34 |